Compiling regional structures in geological databases: The giant quartz veins of the Pyrenees as a case study. (October 2022) - González-Esvertit, Eloi; Canals, Àngels; Bons, Paul D.; Casas, Josep Maria; Gomez-Rivas, Enrique
Abstract: Gathering and arranging specific data related to different types of geological structures in thematic and interactive databases has become central for the geosciences. However, a well-defined workflow to achieve this goal is currently lacking. We present a Geographical Information System-based method for the systematic compilation, evaluation, and interpretation of regional geological structures. The method is demonstrated by indexing 741 giant quartz veins cropping out along the Pyrenees (SW Europe) in a database called GIVEPY (GIant quartz VEins of the PYrenees). The GIVEPY database incorporates information of the geometry, distribution, and statistics of the indexed veins, as well as of their host rocks, and can serve as a starting point for boosting the understanding of giant quartz veins in the Pyrenees and other areas. The first-order structural controls on vein emplacement are hypothesized on the basis of vein distribution and linkage with other brittle and ductile structures, such as faults, folds, shear zones, and regional foliations. Furthermore, we discuss the strengths and limitations of the workflow and its potential application to other geological structures. The GIVEPY database is dynamic and freely available at https://givepy.info/ . Highlights: A workflow for gathering geological structures is proposed. The approach is tested with 741 Giant Quartz Veins located in the Pyrenees. Outcomes are presented as an interactive and open-access database called GIVEPY. The method can be applied to other structures and replicated in different settings. The age of veins and the structural controls on their emplacement are hypothesized.